Desenvolvimento de materiais para fotoelasticidade de reflexão - Oliveira, Sonia Aparecida Goulart de (1988)
This work deal with the development of a material for the photoelastic coating technique, using Brazilian raw materiais. This technique has not been largely used in Brazil owing to difficulties with the importantion of the photoelastic materiais. To obtain the materiais it was used four kinds of epoxy resins and four kinds of amines curing agents as a hardener, all produced by CIBA GEIGY - Química S.A. do Brazil. By the combination of the basic components in different amount, sev- eral composition were obtained. Amoung these, the two ones that showed the best properties for photoelastic coating were chosen. This work describes interily the procedure used to obtain the materiais, the determination of the properties required to ap- ply the technique and shows the general application. During the development of this work, it was also obtained and presented in a particular chapter a new material for bidimensional photo- elasticity, with properties similar to the imported materiais.